2015
DOI: 10.3109/17435390.2014.992816
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of ZnO nanoparticles in mammalian cells: Role of physicochemical transformations under the aging process

Abstract: Zinc oxide nanoparticles (ZnO NPs) potentially undergo physicochemical transformation in the environment, which may lead to unexpected environmental and health risks. The "aging" process is essential for better understanding the toxicity and fate of NPs in the environment. However, the mutagenic effects of aged ZnO NPs are still unexplored. The present study focused on investigating the physicochemical transformation during aging process and clarifying the mutagenicity of naturally aged ZnO NPs in human-hamste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 37 publications
4
23
0
1
Order By: Relevance
“…In spite of, the untreated control cells dying due to the toxicity of 6‐TG, because of functional HGPRT. This is consistent with previous studies of ZnO NP mutagenicity in human‐hamster hybrid (AL) cells (Wang et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…In spite of, the untreated control cells dying due to the toxicity of 6‐TG, because of functional HGPRT. This is consistent with previous studies of ZnO NP mutagenicity in human‐hamster hybrid (AL) cells (Wang et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, NP aging (weathering) affects dissolution and reactivity [13,44,45]. Previously, we reported that ZnO NPs undergo a dramatic physicochemical transformation with aging [22]. Here, we confirm a similar transformation process and the neoformation of Zn 5 (CO 3 ) 2 (OH) 6 (Figure 1).…”
Section: Discussionsupporting
confidence: 75%
“…It is possible that the mechanisms underlying ZnO NP cytotoxicity differ from those underlying ZnO NP mutagenicity. Previously, we revealed that, during the aging process, Zn 2+ ions and solid particles contribute differently to the mutagenicity of ZnO NPs [22]. These observations indicate that the mechanisms of ZnO NP toxicity are complicated and more studies focusing on mutagenicity and NP transformations in the environment are needed.…”
Section: Daysmentioning
confidence: 99%
See 1 more Smart Citation
“…monthly) re-testing of parameters such as size distribution to ensure relevance of the characterisation data to the toxicity data (Izak-Nau et al, 2015 ). Similar impacts of ageing (in Milli Q water) of Zinc oxide NMs on the mutagenicity of the NMs to human-hamster hybrid (AL) cells were found, whereby the ZnO NMs underwent sophisticated physicochemical transformations with aging such as microstructural changes, the formation of hydrozincite (Zn 5 (CO 3 ) 2 (OH) 6 ) and the release of free zinc ions (Wang et al, 2015 ). Interestingly, the aged ZnO NMs resulted in much lower cytotoxicity but a relatively higher degree of mutation than fresh ZnO NMs (Wang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 93%